A facile and rapid route to synthesize CuOx/Ce0.8Zr0.2O2 catalysts with high performance for CO preferential oxidation (CO-PROX). (28th September 2015) - Wang, Jing; Deng, Lian; He, Dedong; Lu, Jichang; He, Suyun; He, Sufang; Luo, Yongming
Abstract CuO(10)–Ce0.8Zr0.2O2-UGC-300 (CuO–Ce0.8Zr0.2O2 prepared by urea grind combustion method, with 10 wt.% CuO loading and calcined at 300 °C) and CuO(10)–Ce0.8Zr0.2O2-IWI-300 (prepared by incipient wetness impregnation method) catalysts were tested for CO-PROX. It was noticed that both the CO conversion and the O2 selectivity of CuO(10)–Ce0.8Zr0.2O2-UGC-300 are higher than those of CuO(10)–Ce0.8Zr0.2O2-IWI-300. The high performance catalytic activities of CuO(10)–Ce0.8Zr0.2O2-UGC-300 have been attributed to the synergistic effects of highly dispersed Cu species together with the stronger interaction between CuO and the support. The effect of the CuO content and calcination temperature on the catalytic activity of the CuO–Ce0.8Zr0.2O2 catalysts were investigated in detail. The catalyst with 10 wt.% CuO loading and calcined at 300 °C exhibited the highest catalytic activity. CuO(10)–Ce0.8Zr0.2O2-UGC-300 catalyst exhibited excellent adaptability of space velocity from 12, 000 h−1 to 36, 000 h−1 and with good tolerance towards CO2 and H2O.